Estimation of triggered‐lightning dart‐stepped‐leader currents from close multiple‐station dE/dt pulse measurements. Issue 4 (18th February 2015) - Gamerota, W. R.; Uman, M. A.; Hill, J. D.; Ngin, T.; Pilkey, J.; Jordan, D. M.
Abstract The modified transmission line model is used to derive the vertically propagating leader‐step currents necessary to radiate measured dart‐stepped‐leader dE/dt pulses from triggered lightning at close range (<400 m) and low altitude (<70 m). The model‐predicted dE/dt pulses were compared with measured dE/dt pulses at nine locations ranging from 27 to 391 m from the channel base for four dE/dt pulses radiated from two triggered dart‐stepped leaders. The dE/dt pulses at the closest station, 27 m, were unipolar, dominated by electrostatic and induction components of the radiated dE/dt, and of opposite polarity to the more distant initial dE/dt peaks. The other, more distant, eight stations exhibited bipolar dE/dt pulses, being more or less dominated by the dE/dt radiation component. The derived leader‐step current has a slow front that precedes a fast transition to peak amplitude followed by a slow decay to zero after several microseconds. For the four modeled dE/dt pulses, the estimated causative leader‐step current peak amplitudes varied from 0.9 to 1.8 kA, the half‐peak widths ranged from 370 to 560 ns, the charge transfers were about 1 mC, and the peak current derivatives were about 10 kA/µs. The upward propagation speeds of the leader‐step current were from 1.1 to 1.5 × 108 m/s with exponential spatial current decay constants from 13 to 27 m. One dE/dt pulse is analyzed in more detail by studying changes in model‐predicted waveforms versus current initiation altitude and by examining the effect of varying model input parameters.